Apoptotic Bodies Restore NAD and Mitochondrial Homeostasis in Fibroblasts - Shutong Qian; Siya Dai; Chunyi Guo; Wenjun Wang; Jiajia Pang; Yichen Shen; Mingyuan Xu; Jie Hu; Wenguo Cui; Xiaoming Sun; Jinghong Xu (Advanced Science)
Abstract Fibrotic skin diseases are characterized by excessive fibroblast proliferation and pathological extracellular matrix deposition. As a pivotal coenzyme in cellular energetics, NAD homeostasis perturbation is implicated in fibrosis. Multiple studies have demonstrated the therapeutic potential of mesenchymal stem cells (MSCs) against cutaneous fibrosis, while the specific mechanism remains elusive. Herein, this work finds that although almost all MSCs undergo in situ apoptosis within 24 h post‐subcutaneous administration, MSC‐derived apoptotic bodies (ABs) mediated potent anti‐fibrotic effects. Mechanistically, ABs can restore NAD and mitochondrial homeostasis through NAMPT transfer, FOXO1 deacetylation enhancement, and PINK1/PARKIN‐dependent mitophagy activation. To achieve penetration into the hard matrix of fibrotic skin, permeable apoptotic bodies (pABs) are constructed via metabolic glycoengineering and copper‐free click chemistry techniques. In both keloid xenograft and scleroderma murine models, pABs can significantly penetrate collagen matrix and reduce skin fibrosis. In summary, this research establishes a highly promising strategy for reversing skin fibrosis with hard fibrotic matrix.